Middleware de serviços multi-camadas para redes de sensores sem fio - Ribeiro, José Eduardo (Universidade Federal de São Carlos, 2010)
Technological evolutions in the microelectronic systems and in the wireless communication allowed the development of devices called sensor nodes, which are smalles have low cost and low energy consumption. The sensor nodes integrate sensing modules, data processing and of wireless communication. The use of sensor nodes in a distributed way makes possible the communication among them providing the formation of the Wireless Sensor Networks (WSN). WSN are being used more and more as powerful monitoring tools of applications of environmental monitoring the monitoring of emergency situations in environments subject to risk situations to the life and the patrimony such as fire, leaks of poisonous gasses and explosions. Emergency management systems that integrate networks of wireless sensors have been used as support to the making of decision for response teams to the emergencies where the response time in these conditions becomes preponderant factor, aiming at the success of rescue practical operations. In order to the system of emergency management to be efficient a support layer to provide integration and reusability of the services is necessary supplied by the system besides a solution to abstract all the communication complexity and data processing inside WSN. In this work a middleware for WSN was designed and partially implemented to aid the work of the developers applications. The main characteristics of this middleware are to supply an expressive and flexible mechanism for subscriptions of interest of the application in the WSN and reusable interfaces that use technologies standard of the Web to provide interoperability between the services and applications. An initial evaluation accomplished with a prototype of some functions of the middleware. An estimate of occupation of memory in the sensor nodes was made with base in studies reported in the literature, and display that middleware projected is viable for the platform of the hardware of motes Mica 2. The mote Mica 2 is the third generation of commercial sensor nodes of the mica family motes, used to enable low energy in WSN.
Keywords: Sistemas distribuídos; Computação pervasiva; Serviços da web; Redes de sensores sem fio; Middleware; Serviços Web; Publish/Subscribe; RSSFs; Middleware; Web Services; Publish/Subscribe; WSN; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO